Exome sequencing and pathogenicity-network analysis of five French families implicate mTOR signalling and autophagy in familial sarcoidosis. Issue 2 (1st August 2019) - Calender, Alain; Lim, Clarice X.; Weichhart, Thomas; Buisson, Adrien; Besnard, Valérie; Rollat-Farnier, Pierre Antoine; Bardel, Claire; Roy, Pascal; Cottin, Vincent; Devouassoux, Gilles; Finat, Amélie; Pinson, Stéphane; et al.
Sarcoidosis is a complex disease characterised by the presence of epithelioid non-caseating granulomatous inflammation affecting multiple organs and whose aetiology has been related to microbial, environmental and genetic factors [1, 2]. However, no single antigenic trigger has been identified, although associations with Propionibacterium acnes and mycobacteria pathogen-associated molecular pattern, deposition of serum amyloid A, and exposure to inorganic particles and insecticides have been suggested [3–5]. Occurrence of familial cases suggests that genetic variation contributes to disease pathogenesis with a heritability of about 39% [6]. Despite intensive genome-wide association studies, no single nucleotide polymorphism is, as yet, able to explain the "missing heritability" in the disease, especially for non-resolving, non-Löfgren syndrome sarcoidosis [5–7]. Sarcoidosis is a multifactorial disease induced by environmental and genetic factors. Whole exome sequencing in 5 familial cases of the disease suggest that genetic defects in Rac1 and mTor functional hubs may be relevant to sarcoidosis pathogenesis .http://bit.ly/2xooHx3